Evolving patterns of care and outcomes in relapsed/refractory FLT3 mutated acute myeloid leukemia adult patients. Issue 11 (19th September 2021) - Boluda, Blanca; Martínez-Cuadrón, David; Algarra, Lorenzo; Cano, Isabel; Sayas, María J.; Acuña-Cruz, Evelyn; Blanco, Albert; Marco-Ayala, Javier; DeLapuerta, Rosalía; Díaz-González, Álvaro; Tormo, Mar; Rodríguez-Veiga, Rebeca; et al.
Abstract: We have analyzed treatment patterns and outcomes of relapsed/refractory(R/R) FLT3mut AML adult patients registered in our institutional data base between 1998 and 2018. Overall, 147 patients were evaluable: 34 from 1998 to 2009, 113 from 2010 to 2018. Salvage treatments were intensive chemotherapy ( n = 25, 74%), and supportive care ( n = 9, 26%) in the 1998–2009 period, and intensive chemotherapy ( n = 63, 56%), hypomethylating agent ( n = 7, 6%), low-dose cytarabine-based ( n = 8, 7%), clinical trial ( n = 16, 14%) and supportive care ( n = 19, 17%) in the 2010–2018 period. Complete remission (CR) or with incomplete recovery (CRi) rate was 44%, 49% among patients treated intensively (vs 30% with non-intensive p = 0.005). Median overall survival since first R/R was 5.8 months, and 16.3 months in subjects receiving an allo-HSCT in CR/CRi after first salvage (vs 3.8 in the remaining patients p < 0.0001). Clinical outcomes of R/R FLT3mut AML remain unsatisfactory. Inclusion in clinical trials and expanding options could lead to improved outcomes.